Learning Processes and Trajectories for the Reduction of Antibiotic Use in Pig Farming: A Qualitative Approach - Nicolas Fortané; Florence Bonnet-Beaugrand; Anne Hémonic; Carole Samedi; Arnaud Savy; Catherine Belloc (MDPI AG, 2015)
Since 2011, French public policy has been encouraging a reduction in the use of antibiotics in animal farming. The aim of this article is to look at how some farms have already managed to lower their consumption of antibiotics, and to highlight the levers of change in farming health practices. Our research uses a qualitative study based on 21 semi-structured interviews with farmers and veterinarians in the French pig-farming sector. We use the notion of "trajectory of change" to examine, over time, the intersection of the technical, economic, social and organisational determinants which affect the reduced use of antibiotics. The "learning process" concept makes it possible to take account of the way in which the actors assimilate, appropriate and implement new health practices. We have identified three interdependent levels of learning: technical learning, cognitive learning and organisational learning.